TIME MANAGEMENT PSYCHOLOGICAL WELL-BEING HOME-LEARING COVID-19 - Fifi Juniarti; Agnes Regina (Psikodidaktika, 2021)
The emergency situation of COVID-19 which driven the policy of social-distnacing in most of society life aspect, including education. The ministry of education applied the policy for education institution must delivery the learning from home as known as home-learning. The condition of online learning as the platform that possible to keep the learning processing keep running had challenge the student, including the increasing duration of screen-time, as the physical activity decreasing, and the others risk factor like grief and economic problem that happened to families. This social condition and online learning process have challenge student’s physical-health and mental-health. This study aims to review the relevance from a strategy of self-regulation, spesifically time-management and psychological well-being that student possess during home-learning in COVID-19 situation. This quantitative correlation research held by online-questionnaire that filled by 281 junior and senior high students in Jabodetabek area. This study show there is correlation between time-management and psychological well-being. The signifincance score at 0,000 (p < 0,05) with the correlation coefficient at 0,543. The time-management strategy discovered had related or contribute positively to student’s psychological well being even in the COVID-19 situation tha brings challenges and uncertainty.